Approximate confidence intervals for the weighted kappa coefficient of a binary diagnostic test subject to a case-control design - Roldán-Nofuentes, J. A.; Amro, R. M. (Journal of statistical computation and simulation, 2017)
Case-control design to assess the accuracy of a binary diagnostic test (BDT) is very frequent in clinical practice. This design consists of applying the diagnostic test to all of the individuals in a sample of those who have the disease and in another sample of those who do not have the disease. The sensitivity of the diagnostic test is estimated from the case sample and the specificity is estimated from the control sample. Another parameter which is used to assess the performance of a BDT is the weighted kappa coefficient. The weighted kappa coefficient depends on the sensitivity and specificity of the diagnostic test, on the disease prevalence and on the weighting index. In this article, confidence intervals are studied for the weighted kappa coefficient subject to a case-control design and a method is proposed to calculate the sample sizes to estimate this parameter. The results obtained were applied to a real example.